The Role of Information Technology in Guidance and Counseling Administration in Schools - Bunga Afasli; Neviyarni S; Firman; Muhammad Asyraf Che Amat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Guidance and Counseling Administration (BK) plays an important role in the smoothness and effectiveness of services provided to students. The completeness of BK administration includes various components such as recording student data, documenting activities, and planning BK programs. Although BK administration is often considered a routine administrative task, its completeness affects the quality of counseling services received by students. This article aims to review the importance of completeness of administration in BK, by discussing the main components that must be present in good and efficient BK administration. In addition, this article also explores the obstacles that are often faced in implementing BK administration in schools and how to solve these problems. Technology also plays an important role in facilitating completeness of administration, by providing a more structured and easily accessible system. Through existing literature, this article emphasizes that the completeness of good BK administration not only supports the counselor's duties in carrying out their functions, but also contributes to improving the quality of guidance services that are more optimal for student development.